English for e-Tourism: Language, Technology, and Tourism - Fitrotul Maulidiyah (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2019)
English is the most widespread and dominant business language and it has become compulsory for people to speak English if they wish to join a global workforce.A number of research show that business communication is most often conducted i English. Due to its skyrocketing use,a tendency for designing specialized courses which focus more on specific outcomes and industries is observed, especially for English department students. By addressing specific audiences and catering for specific needs,English for Specific Purposes (ESP) is the example of this category.This paper focuses on English for e-Tourism and the teaching strategies which are implemented in order to adjust the course to students’ needs. The emphasis is taken into consideration because the relationship between technology and tourism has become delicate and challenging.  Observations on this inseparable relationship assume a great importance when considering the varied world of tourism activities, where the strict dependence on technology for the efficient and effective management of information has caused a real revolution due to the diffusion of online applications. The most recent developments of the web and social networks have then further accentuated the influence of ICTs (Information and Communication Technologies) on the sector of education. Moreover, the important aspects of English for e-Tourism will be highlighted since the adoption of new technologies has reshaped the entire process of tourism service development as well as the entire tourism industry as a whole. Finally, reference will be made to the responsibilities that both teachers and students have in the ESP framework.